2013
DOI: 10.3758/s13414-013-0506-1
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with congenital amusia imitate pitches more accurately in singing than in speaking: Implications for music and language processing

Abstract: In this study, we investigated the impact of congenital amusia, a disorder of musical processing, on speech and song imitation in speakers of a tone language, Mandarin. A group of 13 Mandarin-speaking individuals with congenital amusia and 13 matched controls were recorded while imitating a set of speech and two sets of song stimuli with varying pitch and rhythm patterns. The results indicated that individuals with congenital amusia were worse than controls in both speech and song imitation, in terms of both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 60 publications
(85 reference statements)
9
43
2
Order By: Relevance
“…Given that amusia has been characterized as a deficit of awareness (Paquette, Goulet, & Rothermich, 2013;Peretz, Brattico, J€ arvenp€ a€ a, & Tervaniemi, 2009), the level of explicit awareness of pitch information required for the task may play an important role. However, many studies have reported mixed results regarding whether amusics find direction tasks more difficult than detection tasks (Liu et al, 2013;Liu et al, 2010;Williamson, Liu, Peryer, Grierson, & Stewart, 2012), and the weight of the evidence here indicates that amusics have equal difficulty with change detection and direction tasks. Additionally, all the tasks assessed by our meta-analysis were explicit ones, and it may be that a small difference in degree of explicitness is not enough to elicit effect size differences between change detection and direction tasks across studies.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Given that amusia has been characterized as a deficit of awareness (Paquette, Goulet, & Rothermich, 2013;Peretz, Brattico, J€ arvenp€ a€ a, & Tervaniemi, 2009), the level of explicit awareness of pitch information required for the task may play an important role. However, many studies have reported mixed results regarding whether amusics find direction tasks more difficult than detection tasks (Liu et al, 2013;Liu et al, 2010;Williamson, Liu, Peryer, Grierson, & Stewart, 2012), and the weight of the evidence here indicates that amusics have equal difficulty with change detection and direction tasks. Additionally, all the tasks assessed by our meta-analysis were explicit ones, and it may be that a small difference in degree of explicitness is not enough to elicit effect size differences between change detection and direction tasks across studies.…”
Section: Discussionmentioning
confidence: 55%
“…The application of all selection criteria resulted in the inclusion of 43 unique articles. One of these articles (Liu et al, 2013) was dropped from the database because it reported the same pitch threshold data (for the same set of participants) as another article that was already included ).…”
Section: Inclusion and Exclusion Criteria For Databasementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, difficulties with music are not the only characteristics of individuals with amusia (amusics). Studies have shown that the perception and production of pitch changes in the linguistic domain may likewise be problematic for amusics, although to a less pronounced extent (e.g., Patel et al, 2008;Liu et al, 2010;Tillmann et al, 2011a;Liu et al, 2012;Thompson et al, 2012;Liu et al, 2013). However, the precise nature of amusia, or rather, of the deficits that underlie amusia, is not well understood.…”
Section: Introductionmentioning
confidence: 93%
“…Accordingly, a domain-general point of view has been used to explain amusics' pitch perception deficits in both music and language. Indeed, the abilities of amusics to perceive pitch and to control pitch production are poorer than their non-amusics counterparts, especially when the pitch variation is comparatively small, e.g., intonation contours (Patel et al, 2008;Liu et al, 2010;Hutchins and Peretz, 2012;Liu et al, 2012), lexical tones (Nguyen et al, 2009;Nan et al, 2010;Tillmann et al, 2011a;Liu et al, 2012;Liu et al, 2013), as well as the prosodic cues associated with specific emotional states . a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 98%